Stray cattle management and their economy - Somagond, Arun; Patel, B H M; Biswal, Prachurya; Dutt, Triveni (Indian Farming, 2021)
Stray should not be considered as burden to the society. It must be managed in scientific way in special shelter farm with purpose of conserving our indigenous breed as these breeds are resistant to heat stress and teak problems and protects our biodiversity which ultimately maintain ecosystem.